PENERAPAN MODEL PEMBELAJARAN KOOPERATIF PENDEKATAN STRUKTURAL THINK PAIR SQUARE (TPS) UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA SISWA DI KELAS VIII.7 SMP NEGERI 20 PEKANBARU - Rachmad, Sadiyah; Heleni, Susda; Solfitri, Titi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: The background of this research is mathematics learning outcomes to low. This research aims to improve the learning process and improve the student’s mathematics learning outcomes through the implementation of Cooperative Learning with Think Pair Square Approach. This type of research is the Classroom Action Research with two cycle. The research was conducted in class VIII.7 SMPN 20 Pekanbaru in the second semester of the 2015/2016 academic year with the subject of as many as 40 students. The research instrument consists of learning devices and instrument data collectors. Learning device used in this research is the Syllabus, RPP and LKS. The instrument data collector used in this research is the observation sheet and math achievement test. Data analysis technique used is descriptive statistical analysis of quantitative data. Based on the data analysis, the percentage of students who achieve KKM on base score is 17 students with a percentage of 42.5% and increased in Kuis I of 21 students with a percentage 52.5% and also an increase in Kuis II at 26 students with a percentage 65%. So, result of the research showed that, the learning process has improved and the student’s mathematics learning outcomes in class VIII.7 SMPN 20 Pekanbaru also increased after applying the Cooperative Learning with Think Pair Square Approach. Cooperative Learning with Think Pair Square Approach can be used as an alternative in learning, because it can improve the learning process and improve the student mathematics learning outcomes.Keywords: Cooperative Learning, Think Pair Square Approach, Learning Process, Student Mathematics Learning Outcomes